A comparative study on the dynamic behaviour of 10 MW conventional and compact gearboxes for offshore wind turbines. Issue 7 (21st December 2020) - Wang, Shuaishuai; Nejad, Amir; Bachynski, Erin E.; Moan, Torgeir
Abstract: This study compares the dynamic behaviour of a conventional and a compact gearbox for the DTU 10 MW wind turbine supported on a monopile offshore structure. The conventional gearbox configuration is composed of two planetary epicyclic stages and one parallel stage, while the compact gearbox configuration consists of a fixed planetary stage and a differential compound epicyclic stage. The design methodology for these two gearboxes is described, and the final gearbox specifications show a lighter weight and smaller volume for the compact gearbox design compared to the conventional one. Computational gearbox models are established using the multi‐body system dynamic analysis method. A decoupled approach is employed for the gearbox load effect analysis. Comparisons of the dynamic behaviour between these two gearboxes are conducted under pure torque load cases, tangential pin position error conditions and non‐torque load cases. The results demonstrate that the compact gearbox has better dynamic performance under different torque load cases and is more robust to withstand the effects of manufacturing errors and rotor non‐torque loads compared to the conventional gearbox. It is believed that the proposed compact gearbox concept is promising and would be a good alternative for multi‐megawatt floating wind turbines, although challenging with respect to the design and operation complexity.